PENGELOLAAN SUMBERDAYA IKAN EKONOMIS PENTING DI KABUPATEN CIREBON JAWA BARAT - Fidhiani, Dayang Dyah (Jurnal Harpodon Borneo, 2011)
Result catches fish of white pomfret (Pampus argentus) and fish of white snapper (Lates calcarifer) contributed significantly to improving the welfare of fishermen, especially Cirebon regency of West Java. The study aimed to estimate the optimal utilization and to formulate models of fisheries management. To pass estimation and management model used Model bioeconomy.  The results obtained from the estimated balance of the bioeconomy optimum utilization of fishery resources fish of white pomfret (Lates calcarifer) the Harvest of 707,18 kg/year, efforts of 7063,49 trips/year, and Phi of Rp.15.824.173, 45/year  and fish of white snapper (Pampus argentus) the Harvest of 280,96 kg/year, efforts of 2660,20 trips/year, and phi of Rp.2.400.882,73/year and then be created for the formulation of economic models of resource management fish of white pomfret and white snapper optimal and sustainable in Cirebon regency is the management regime based on sole owner/MEY (maximum economic yield) to form the optimal management of effort and catch.